2012
DOI: 10.1519/jsc.0b013e318231a627
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Responses to Impact and Collision During Elite Rugby League Match Play

Abstract: The purpose of this study was to investigate the relationship between the prematch and short-term postmatch neuromuscular responses to the intensity, number, and distribution of impacts associated with collisions during elite Rugby League match play. Twenty-two elite male Rugby League players were monitored during 8 regular season competition matches using portable global positioning system (GPS) technology. The intensity, number, and distribution of impact forces experienced by players during match play were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(143 citation statements)
references
References 24 publications
8
124
1
Order By: Relevance
“…Research in rugby league has shown no relationship between contact events (tackles and hit-ups) and accelerometer measures 19 , but did show that accelerometer measurements were correlated with decreases in peak rate of force development and International Journal of Sports Physiology and Performance F o r P e e r R e v i e w 9 peak power up to 24 h post match. These findings indicate that even though accelerometer measures do not match up with the number of contact events that players are exposed to during rugby union match play, they may be an important indicator of physical load.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research in rugby league has shown no relationship between contact events (tackles and hit-ups) and accelerometer measures 19 , but did show that accelerometer measurements were correlated with decreases in peak rate of force development and International Journal of Sports Physiology and Performance F o r P e e r R e v i e w 9 peak power up to 24 h post match. These findings indicate that even though accelerometer measures do not match up with the number of contact events that players are exposed to during rugby union match play, they may be an important indicator of physical load.…”
Section: Discussionmentioning
confidence: 91%
“…Waldron et al 18 showed the reliability of accelerometer measures to be acceptable (CV = 4.7-5.2%). Research has shown correlations between high intensity impacts (>8G) and markers of muscle damage 16 , as well as neuromuscular markers of post-match fatigue 19 in rugby league. These results show that accelerometer data may be an indicator of the overall mechanical load that players are exposed to.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 81 player observations were used for analysis, 43 for the forwards and 38 for the backs. Each player was involved in a minimum of 75% of the total game time (McLellan and Lovell, 2012). Ethical approval was granted by the University ethics committee and written informed consent was acquired from participants along with parental consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Researchers have not shown any correlation between high-intensity impacts and collision events like tackles during rugby league matches. [16] Despite this, research has shown correlations between high-intensity impacts (>8G) and markers of muscle damage [17] , as well as neuromuscular markers of post-match fatigue [16] in rugby league. Accelerometer data have not previously been reported in elite rugby union competitions, and may be of some value in terms of quantifying physical impacts sustained and planning recovery strategies.…”
mentioning
confidence: 99%